Peningkatan, Hasil belajar, Mode PENINGKATAN HASIL BELAJAR IPA SISWA KELAS IV MELALUI MODEL PENGAJARAN TERBALIK - Sundahry Dahry (Jurnal Tunas Pendidikan, 2020)
Abstract The purpose of this study is to describe the improvement of student learning outcomes through the fourth grade reciprocal teaching down in SDN 19 Sungai Talang Tarusan. This research is a classroom action research, the subject of the fourth grade students of SDN 19 Sungai Talang Tarusan totaling 28 students. The research was conducted in the second semester of the 2015/2016 Academic Year. Instrument used is the observation sheet activities of teacher, student assessment sheets affective, psychomotor student assessment sheets and sheets of test results of students' cognitive learning. Implementation science learning through reciprocal teaching class IV is progressing well. Based on the research, the results of cognitive learning level of knowledge in the first cycle is increased in the second cycle of 78.2 to 87.6, the results of cognitive learning levels of understanding in the first cycle 69.1 increase in cycle II to 84.3, results in the affective domain 1 62.5 cycles and increased in the second cycle becomes 83.7, the results of the first cycle psychomotor 64.3 increase in cycle II to 83.9. This means learning science through teaching model upside down to improve learning outcomes of fourth grade students of SDN 19 Sungai Talang Tarusan. Based on this study, it can be concluded that the reciprocal teaching to improve learning outcomes IPA fourth grade students of SDN 19 Sungai Talang Tarusan South Shore. Keywords: Improvement, learning outcomes, Reciprocal Teaching, IPA